2018
DOI: 10.1371/journal.pone.0195422
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative validation of nicotine production in tea (Camellia sinensis L.)

Abstract: Endogenous nicotine was confirmed to be present in tea plants (Camellia sinensis L.) by liquid chromatography-tandem mass spectrometry of tea samples from tea-producing regions in six Asian countries. All samples contained nicotine (0.011–0.694 μg g−1 dry weight). Nicotine contents remained constant during manufacturing of green, oolong and black teas, implying that nicotine is stable against heating, drying, enzymatic oxidation and mechanical damage during processing. Flower buds and seeds of cultivar Yabukit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…These rather low concentrations, without any hint of biological activity are also known for other (food plants) like tea ( Camellia sinensis ), carrot, pear, strawberry or plants from the Solanaceae family (besides the well‐known Nicotiana spp. which shows extremely high values in the g/kg range) …”
Section: Resultsmentioning
confidence: 96%
“…These rather low concentrations, without any hint of biological activity are also known for other (food plants) like tea ( Camellia sinensis ), carrot, pear, strawberry or plants from the Solanaceae family (besides the well‐known Nicotiana spp. which shows extremely high values in the g/kg range) …”
Section: Resultsmentioning
confidence: 96%
“…Other possible explanations include diet and/or pollution. Low levels of nicotine are present in a number of frequently consumed vegetables, more specifically of the Solanaceae and Brassicaceae family (eggplant, bell peppers, chili peppers, potatoes, tomatoes, tomatillos, and cauliflower), as well tea leaves 27,28 . On average, each fresh fruit of this vegetables contains nicotine at 2–7 μg/kg, and dietary sources may provide a maximum intake of 2.25 μg/day.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of nicotine are present in a number of frequently consumed vegetables, more specifically of the Solanaceae and Brassicaceae family (eggplant, bell peppers, chili peppers, potatoes, tomatoes, tomatillos, and cauliflower), as well tea leaves. 27 , 28 On average, each fresh fruit of this vegetables contains nicotine at 2–7 μg/kg, and dietary sources may provide a maximum intake of 2.25 μg/day. Consumption of these plants for many years could explain the low cotinine level detected in our nonsmoker participants, who reported daily consumption of these foods.…”
Section: Discussionmentioning
confidence: 99%
“…As an aqueous product extracted from C. sinensis, tea has become one of the most popular beverages due to its pleasant flavor, taste, and bioactive ingredients for health (Ikka et al, 2018;Li et al, 2015). Previous studies have reported that tea leaves contain important bioactive compounds such as polyphenols, alkaloids, caffeine, and theanine.…”
Section: Introductionmentioning
confidence: 99%